Investigation of cemented carbides with alternative binders after CVD coating. (January 2017) - Toller, Lisa; Liu, Chunxin; Holmström, Erik; Larsson, Tommy; Norgren, Susanne
Abstract: Due to health concerns surrounding the use of cobalt as a binder for tungsten carbide in cemented carbides there is a drive to find an alternative binder. Although there are many publications on cemented carbides with alternative binders very few consider the possibility to coat these materials. In this work four different binder compositions containing iron-nickel or iron-nickel-cobalt and a pure cobalt reference are investigated with respect to coating ability. It is shown that it is possible to coat these cemented carbides with alternative binders through the same chemical vapor deposition process that is commonly used for cobalt based inserts and get similar coating structure. It is further shown that it can be done without the formation of η-phase and with comparable scratch test adhesion. Highlights: Scratch tests gave comparable adhesion for multilayer CVD coatings on cemented carbides with alternative and cobalt binders. Bulk hardness alone could not explain the differences found in scratch test adhesion. The results of this study are promising for further development of coated cemented carbide tools with alternative binders.